MEXICO: PROCESS AND INSTALLATION OF A NEW POLITICAL REGIMEN (Andamios, Revista de Investigación Social, 2009)
In the eighties, Mexico vacillated between two political regimes: one, statist, populist, and authoritarian, and the other neoliberal, technocratic, and less authoritarian. The interest of powerful business groups, Mexican and foreign, who adopted neoliberal dogma, was sufficient to install Carlos Salinas de Gortari, via the “new” Partido Revolucionario Institucional (PRI) in the presidency in a fraudulent election in 1988. The technocracy, first with the PRI and later with the Partido de Acción Nacional (PAN), grabbed power and retained it, carrying out a coup d’ etat ex ante against Andrés Manuel López Obrador to keep him from winning the presidency in 2006. The reason is not hard to understand: this candidacy represented something that the power elites were not willing to concede: that the new régimen would be toppled to return to one with more state intervention and protection of national sovereignty, especially in maters of control of energy resources.The dilemma of the two overlapping regimes was resolved, with scams and frauds, from the upper echelons of power, in favor of technocratic neoliberalism, under the control of the right-wing PAN since 2000. The major problem is that the center-left party of Cuauhtémoc Cárdenas and López Obrador, doesn’t seem to be up to the historical challenge that it faces.
Keywords: Mexico; political regimens; technocracy; neoliberalism